COMPARISON OF BLOOD GLUCOSE LEVELS IN TUBERCULOSIS PATIENTS DURING THE INITIAL AND CONTINUATION PHASES OF TREATMENT AT X HOSPITAL, TANGERANG CITY - Citra Trisna; Septiatul Awaliah; Mardyana Nizar; Aminah Aminah (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Abstract. Tuberculosis remains a major global health problem and continues to be one of the leading causes of death from infectious diseases, even in developed countries. The administration of anti-tuberculosis drugs (OAT) is divided into two phases: the initial phase and the continuation phase. However, the use of OAT is not without side effects, as its duration of use may influence blood glucose levels. This study aimed to examine differences in blood glucose levels among tuberculosis patients undergoing the initial and continuation phases of treatment at X Hospital in Tangerang City. A comparative study design was employed to compare two groups with distinct treatment phases. Samples were selected through purposive sampling, consisting of 30 participants: 15 in the initial phase and 15 in the continuation phase. Fasting blood glucose levels were measured using the POCT method, and data were analyzed with the Mann-Whitney test. The percentage of abnormal fasting blood glucose results in the initial treatment group was 27%, compared to 67% in the continuation group. Based on the Mann-Whitney test, a p-value of 0.006 was obtained (p < 0.05), indicating a significant difference in blood glucose levels between tuberculosis patients in the initial and continuation phases of treatment